The effects of agitation and aeration on the degradation of sago effluent - Ikhwan Fadzli, Che Ghazali (Universiti Malaysia Sarawak (UNIMAS), 2004)
Sago eftluents were produced during sago processing to obtain sago flour. These wastes contain high BOD and TSS. The waste produced was discharge directly without any treatment. This study was carried out to observe the effects ofagitation and aeration on the degradation of sago effluent. Sago effluents undergo agitation and aeration treatment for 32 days. Effects of agitation and aeration treatments on filtered and crude sago effluent were observed. At the end of the treatment, both treatments were successful on the removal of BOD and reduction of suspended solids. The BOD level was reduced from 140 mg/L to 69.33 mg/L for filtered sago effluent and 126.67 mg/L to 62.67 mg/L for crude sago effluent under aeration treatment, respectively. The BOD level reduced from 141.33 mg/L to 70.67 mg/L and 128 mglL to 68 mg/L under agitation treatment for filtered and crude sago effluent respectively. The TSS level were also reduced for both aeration and agitation treatment. TSS level for filtered and crude sago effluent is reduced from 6.92 to 5.46 and 24.65 -14.91 mg/L under aeration treatment for filtered and crude sago effluent, respectively. The T S level for agitation treatment was reduced from 4.88 mg/L to 5.004 mg/L and 22.882 mg/L to 23.6 mg/L for filtered and crude sago effluent, respectively. Through this study, aeration treatment reduced the pollutant parameter efficiently compared to agitation treatment and filtered sago effluent can undergo treatment faster than crude sago effluent.